Smartphone intrusion and work-life balance among the working emerging adults: The moderating role of perceived sense of control - Chegne, Shuh Ting (2022)
Today, smartphone is more than just a device but as an extended version of oneself. With work, leisure and communication all done from one device, the borders of work and non-work has then become blurred, any undesired spill over may trigger an imbalance in the work-life of the working emerging adults. The purpose of this study is to determine the prediction of smartphone intrusion, perceived sense of control and work-life balance among the emerging adults. A non-probability, convenient and purposive sampling is used and self-administering questionnaires were distributed via online platform. A total of 224 responses were collected from working emerging adults. The data collected were then analysed with Multiple Regression Analysis and PROCESS Macro. The findings of this study shows that the increase in smartphone intrusion was able to negatively predict the work-life balance of the working emerging adults. The results of this study also shows that perceived sense of control moderates the smartphone intrusion for personal leisure during work. However, the moderating factor of perceived sense of control was not significant for smartphone intrusion for work during personal hours. This study was able to contribute to the growing literature on the working emerging adults.